2014
DOI: 10.1103/physreva.89.062316
|View full text |Cite
|
Sign up to set email alerts
|

Generation of universal linear optics by any beam splitter

Abstract: In 1994, Reck et al. showed how to realize any unitary transformation on a single photon using a product of beam splitters and phase shifters. Here we show that any single beam splitter that nontrivially mixes two modes also densely generates the set of unitary transformations (or orthogonal transformations, in the real case) on the single-photon subspace with m 3 modes. (We prove the same result for any two-mode real optical gate, and for any two-mode optical gate combined with a generic phase shifter.) Exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 24 publications
0
59
0
1
Order By: Relevance
“…States (27) are, respectively, the = 1, m = 0 (triplet) state and the = 0, m = 0 (singlet) state, which can be obtained from the usual theory of two-mode systems in terms of angular momentum. The interferometric input and output states can be expanded in terms of |Ψ ± , and the effect of permuting frequencies of the output state is determined from the permutation of frequencies on |Ψ ± .…”
Section: A Two Monochromatic Photonsmentioning
confidence: 99%
“…States (27) are, respectively, the = 1, m = 0 (triplet) state and the = 0, m = 0 (singlet) state, which can be obtained from the usual theory of two-mode systems in terms of angular momentum. The interferometric input and output states can be expanded in terms of |Ψ ± , and the effect of permuting frequencies of the output state is determined from the permutation of frequencies on |Ψ ± .…”
Section: A Two Monochromatic Photonsmentioning
confidence: 99%
“…which is the core requirement for the network designs of [15,16] to decompose any arbitrary unitary. It should be noted that in principle any fixed beamsplitter transformation mixing a pair of optical modes densely generates SU(N ) [31]. However, for practical purposes it is more efficient to implement a network scheme allowing to program the required unitary.…”
Section: A Physical Examplementioning
confidence: 99%
“…The exact permanent case is known to be #P complete even for binary entries, Utj e {0,1} [35], There is also a known algorithm for efficiently approximating a permanent if the matrix has entries consisting of only non negative real numbers. In the same work, it is shown that for a matrix with even a single negative entry, an efficient approximation algorithm would allow one to compute an exact {0,1} permanent efficiently [36], Although having to compute a difficult permanent is a necessary but not sufficient condition for computational hardness, since SO(w) is considered to be universal for linear optics [37], there is no such complexity gap between unitary and orthogonal matrices.…”
Section: B Complexity Concernsmentioning
confidence: 95%